PENGATURAN PENGADAAN BARANG/JASA PEMERINTAH DENGAN UNDANG-UNDANG: PRESIDENTIAL REGULATION OR ACT? - Sri Agung Baskoro; Umbu Rauta; Theofransus Litaay (Refleksi Hukum: Jurnal Ilmu Hukum, 2024)
This article aims to discuss the issue of the appropriate form of legal product for regulating government procurement of goods/services. The existing legal product is the Presidential Regulation, in this case, Presidential Regulation Number 16 of 2018. Considering the material content covered by the Presidential Regulation, this article proposes that regulating government procurement of goods/services should be an Act because there is no explicit delegation from the Act that orders government procurement of goods/services to be regulated by Presidential Regulation. Presidential Regulation Number 16 of 2018 uses an implicit delegation technique that is strengthened by the function of the Presidential Regulation as a legal instrument in exercising the executive power of the President, according to Act Number 12 of 2011. Such an approach is inappropriate because implicit delegation is not law. Furthermore, the Presidential Regulation also contains material content in the form of sanctions. Therefore, the ideal form of legal product for regulating government procurement of goods/services is an Act.